The 125–150 Ma high-resolution Apparent Polar Wander Path for Adria from magnetostratigraphic sections in Umbria–Marche (Northern Apennines, Italy): Timing and duration of the global Jurassic–Cretaceous hairpin turn - (:unkn) unknown (My University, 2007)
A new high-resolution Apparent Polar Wander Path (APWP) segment has been obtained from the magnetostratigraphy of four Kimmeridgian to Lower Aptian sections in the Northern Apennines (Italy). The use of paleomagnetic data for determination of the Adria APWP was hampered by the large local rotations linked to Apennine tectonics, characterized by folds and thrusts developed during the Neogene. To overcome this problem, we have computed relative rotations between time overlapping sections and realigned them in a common declination reference frame (namely the Bosso section). We synthesized a new high-resolution 150 to 125 Ma APWP for Adria, which has a similar shape to the time-equivalent segment of the synthetic APWP of Africa of Besse and Courtillot [J., Besse, V., Courtillot, Apparent and true polar wander and the geometry of the geomagnetic field over the last 200 Myr, J. Geophys. Res. 107(B11) (2002), doi:10.1029/200JB000050]. A 26° clockwise rotation of our combined Adria APWP places it in almost perfect overlap with African data of same age, confirming that the Adria promontory moved coherently with Africa during this time span, whereas the counterclockwise rotation of Adria with respect to Africa was introduced later, most probably during Apennines orogenesis. Finally, we discuss in relation with worldwide plate evolution the peculiar shape of our APWP, which displays a hairpin turn during Berriasian time, and dates the main Late Jurassic/Early Cretaceous change in plate motion at around anomaly M16.
Keywords: African Research